Pharmaceutical care in the use of vitamin-mineral complexes for women during pregnancy and lactation - TemirovaОlena; Bondarenko, Alina; Khaitovych, Mykola (The Ukrainian Scientific Medical Youth Journal, 2022)
during pregnancy and breastfeeding, the need for micronutrients increases, and their insufficient supply negatively affects both the health of the woman and the development of the child. However, the irrational use of large doses of certain vitamins and minerals has risks comparable to their deficiency. The purpose of this study: is to investigate the role of pharmaceutical care in the use of vitamin and mineral complexes for women during pregnancy and breastfeeding based on a questionnaire. The study involved 100 women of different ages. Most respondents lived in cities (90 %). Almost 60 % of women had one childbirth, 25 % had two and 7 % had three childbirths. It was found that about 90 % of respondents breastfeed. Almost half of the women surveyed developed symptoms of hypovitaminosis during pregnancy/breastfeeding. Respondents observed such symptoms of hypovitaminosis as changes in the structure and loss of hair (70 %), changes in the structure of nails (40 %), and the development of dermatitis (27 %). However, no statistically significant differences were found between the incidence of hypovitaminosis symptoms in breastfeeding and non-breastfeeding women. Whereas women over the age of 26 were more likely to experience symptoms of hypovitaminosis compared to younger women (p<0.05). It was found that 97 % of respondents took vitamin and mineral complexes for normal fetal development (81 %), prevention (29 %), and treatment (28 %) of hypovitaminosis, in acute respiratory viral infections (7 %). About 77 % of women took the complex throughout pregnancy, during lactation – 22 %. Respondents took vitamin and mineral complexes as prescribed by a doctor (75 %), recommendations from Internet resources (13 %), advice from a pharmacist (10 %), and relatives/acquaintances (9 %). The choices were: folic acid (65 %), «Elevit Pronatal» (42 %), iron (25 %), «Vitrum Prenatal», and «Femibion» (12 %). Most respondents used vitamin and mineral complexes as a course (86 %), while 15 % took to normalize the condition, 4 % – one month. Almost half of the surveyed women (48 %), mostly those who noted the appearance of symptoms of hypovitaminosis (p<0.05), took several vitamin and mineral supplements. While more than 60 % in the complex took other groups of drugs. It was found that most respondents believe that vitamin and mineral supplements are safe for use in women during pregnancy and lactation. However, almost 10 % noted the appearance of complications after their use, namely: hair loss, changes in nail condition, dermatitis, and indigestion. Therefore, providing quality pharmaceutical care in the release of vitamin and mineral complexes for women during pregnancy and lactation is an important condition for safe and effective pharmacotherapy. Pharmacists influence the rational choice of vitamin-mineral complexes, prevent their uncontrolled use, and provide recommendations on the mode and duration of administration and the peculiarities of interaction with other drugs and foods.